Sol-Gel preperation of 58S and 77S bioactive glass based on decon surfactant - Tan, Shu Er (2015)
Bioactive glasses are biocompatible materials which have been extensively investigated for development and advancement of tissue engineering and medical implantation. There are various kind of bioactive glasses and many different pathways for the production. Sol-gel preparation of 58S and 77S bioactive glasses had been chosen for this study. These two 585 and 775 bioactive glasses consist of different percentage of compositions in SiO₂CaO-P₂0s system. Besides investigated the preparation of bioactive glasses, this study was focused on the effect of different temperature used in thermal treatment on the bioactivity of bioactive glasses. After accurate amount of the precursors were added, Decon® surfactant was added to foam the sol obtained. The foamed gel is then aged, dried and calcinated under suitable temperature and period. Simulated body fluid was used to represent the body fluid for the in-vitro study of bioactivity of produced bioactive glasses. The formation of hydroxycarbonate apatite clusters or layer on the surface of bioactive glasses indicated that the produced bioactive glasses was eligible for the tissue growth. From this study, it was found that after immersion of simulated body fluid solution, the intensity of hydroxycarbonate apatite clusters formed on the 600°C calcinated bioactive glasses was higher as compared to the other calcinated bioactive glasses. Hence, the most optimal calcination temperature for 58S and 77S bioactive glasses was 600°C.